1988
DOI: 10.1200/jco.1988.6.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the utility of a radioimmunoassay for serum CA 19-9 levels in patients before and after treatment of carcinoma of the pancreas.

Abstract: By radioimmunoassay we determined circulating levels of a tumor-associated antigen, CA 19-9, in 47 patients with pancreatic adenocarcinoma, to learn if serial testing was useful in predicting prognosis or in detecting disease progression. Before treatment, 42 (89%) had an abnormal serum level, and 45 (96%) had an abnormal level at some time during the disease course. A pretreatment value of less than 1,000 U/mL (normal, less than or equal to 37 U/mL) was found in 38 patients; 20 (53%) had resectable disease. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(65 citation statements)
references
References 17 publications
3
60
0
2
Order By: Relevance
“…Thus, 2 of 12 patients with elevated serum CA19-9 levels had CCA, versus 2 of 14 patients whose serum CA19-9 levels were within the reference range (P = NS), Sensitivity for serum (2419-9 levels greater than twice the reference range is SO%, specificity is 54.5%. Positive predictive value for this cut-off value is 16.6%. There was no significant gender difference between the two groups (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…Thus, 2 of 12 patients with elevated serum CA19-9 levels had CCA, versus 2 of 14 patients whose serum CA19-9 levels were within the reference range (P = NS), Sensitivity for serum (2419-9 levels greater than twice the reference range is SO%, specificity is 54.5%. Positive predictive value for this cut-off value is 16.6%. There was no significant gender difference between the two groups (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…CA19-9 is a sialylated Lewis blood group antigen targeted by the monoclonal antibody 1116 NS 19-9 (Koprowski et al, 1979). Previous studies have demonstrated a prognostic role for pretreatment CA19-9 in patients receiving radiotherapy or undergoing pancreatic resection (Glenn et al, 1988). Although a small number of papers have described a fall in CA19-9 to be an independent prognostic variable for survival (Gogas et al, 1998;Saad et al, 2002;Stemmler et al, 2003;Ziske et al, 2003), there have been surprisingly few studies investigating the use of baseline CA19-9 in predicting survival for patients with inoperable pancreatic cancer who undergo systemic chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most sensitive and specific serum marker for pancreatic cancer (Pleskow et al, 1989;Rollhauser and Steinberg, 1998). The prognostic value of CA 19-9 for patients with pancreatic cancer treated by resection or radiotherapy is well established (Glenn et al, 1988;Katz et al, 1998;Rollhauser and Steinberg, 1998), but only few data regarding the prognostic value of CA 19-9 during chemotherapy with gemcitabine have been published so far. No prospective studies comparing clinical benefit response and CA 19-9 response were performed.…”
mentioning
confidence: 99%